2017
DOI: 10.5232/ricyde2017.05002
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable critical moments and way of facing them from the futsal coach’s point of view through ad hoc questionnaire. [Momentos críticos desfavorables y manera de afrontarlos desde la perspectiva del entrenador de futsal a través de un cuestionario ad hoc].

Abstract: In this study, a designed ad hoc questionnaire was constructed and validated to investigate the opinion of coaches about the concept of unfavorable critical moment in futsal, and the coincident use of goalkeeper as an outfield player strategy (5vs4) with that critical moment, which is a decisive step towards theoretical and methodological convergences. A total of 129 coaches belonging to teams of divisions 1st, 2nd and 2nd B participated in the questionnaire, which was validated by the judgment of experts thru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(36 reference statements)
0
1
0
2
Order By: Relevance
“…Sin embargo, el fútbol sala ha sufrido una reducción en el número de goles por partido producto de los cambios en el reglamento, como la ejecución del saque de banda, saque de esquina, el tiempo de posesión del guardameta en su propio campo, entre otras; las cuales han afectado directamente el rendimiento (Cachón et al, 2014;Méndez et al, 2017;Zagalaz, 2012) con un descenso en la media de goles por partido (Álvarez et al, 2018).…”
Section: Muestraunclassified
“…Sin embargo, el fútbol sala ha sufrido una reducción en el número de goles por partido producto de los cambios en el reglamento, como la ejecución del saque de banda, saque de esquina, el tiempo de posesión del guardameta en su propio campo, entre otras; las cuales han afectado directamente el rendimiento (Cachón et al, 2014;Méndez et al, 2017;Zagalaz, 2012) con un descenso en la media de goles por partido (Álvarez et al, 2018).…”
Section: Muestraunclassified
“…Contudo, verifica-se que o instrumento proposto por Souza (2002) estaria desatualizado devido à alteração da regra do futsal no ano de 2011, que permitiu a utilização do goleiro como o quinto jogador de linha no campo ofensivo durante o ataque. A utilização do goleiro no ataque para obtenção de superioridade numérica (5x4) é uma manobra frequentemente utilizada pelos técnicos para enfrentar os momentos críticos do jogo (Méndez-Domínguez et al, 2017). Por outro lado, embora o sistema ofensivo 3-1 seja frequentemente utilizado durante as partidas de futsal, é evidente que na interação ataque-defesa, as equipes de futsal utilizem diversos sistemas táticos ofensivos que possibilitem a conservação da posse de bola, a progressão para o objetivo, criação de desequilíbrio defensivo e oportunidades de finalização (Silva et al, 2011).…”
Section: Introductionunclassified
“…Previous research on team sports has also analysed the effect of some Critical Moment Variables (CMV) such as match status, play time and game criticality on variations of game dynamics (Navarro, Lorenzo, Gómez, & Sampaio, 2009;Sampaio, Lorenzo, & Ribeiro, 2006). In Futsal, the analysis of Critical Moments (CM) revealed how match status, play time and fouls committed constrained shooting chances (Méndez, Gómez, Rúiz, & Travassos, 2019), but also constrained coaches to adopt the 5vs4+ GK game strategy (Méndez, Gómez-Ruano, Ruiz, & Cui, 2017). Particularly, it was observed that when a disadvantaged match status of one goal or more occurs, this game strategy was preferentially adopted (Barbosa, 2011).…”
Section: Introductionmentioning
confidence: 99%